Korelasi Self- Confident dengan Hasil Belajar: Analisis Statistik Hasil Belajar Bahasa Arab Siswa SMP al-Ashriyyah Nurul Iman Parung – Bogor - Isyanto, Nur; Parhan, Parhan; Ikhwan, Subaiki; Sidik, Alan Muhamad Taofik Maulana (Ta'limi | Journal of Arabic Education and Arabic Studies, 2024)
Pasca pandemic, there are still many students who lack self-confidence in themselves. This lack of self-confidence, among other things, is usually caused by internal or external factors. And there are still student problems where the students are less responsible in lessons. This research was conducted at Al Ashriyyah Nurul Iman Parung Middle School, Bogor, with the aim of finding out whether there was relationship between self-confidence and the Arabic language learning outcomes of Al Ashriyyah Nurul Iman Parung Middle School students, Bogor. The method used is a quantitative approach, using correlational techniques. The sample used in this research was a saturated sample using all 59 class VIII G students as research respondents. For data collection, researchers used instruments in the form of questionnaires for variable This is shown by the strength of influence or correlation coefficient of 0.523 at a confidence level of 95% (α = 0.05), while the magnitude of the influence or R-square coefficient of determination is 27.35, which means that self-confidence has an influence on learning outcomes. amounting to 27.35% and means the remaining 72.65% is determined by other factors. For the direction of influence or regression coefficient, Ŷ = 42.077 + 0.652.